2011
DOI: 10.1007/s00374-011-0649-y
|View full text |Cite
|
Sign up to set email alerts
|

Exophiala sp.LHL08 association gives heat stress tolerance by avoiding oxidative damage to cucumber plants

Abstract: Exophiala sp. LHL08, a gibberellin-producing strain, was investigated to assess its effects on cucumber plant growth and heat (40°C) stress tolerance. The results reveal that Exophiala sp. associated plants had significantly higher plant growth attributes (shoot length, plant biomass, chlorophyll contents, and leaf area) than control under heat stress. Endophytic association helped the plants to obtain adequate water to reduce the leaf electrolytic leakage under stress. High-temperature-induced oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 69 publications
2
15
1
Order By: Relevance
“…In the current study, the combination of gibberellin and IAA-producing endophyte (e.g. G. geotrichum) with BC increased fatty acid content; however, various studies obtained the same results for the association of endophytic fungi with their host plants (Khan et al, 2012a;2012b). In these and other studies, the production of secondary metabolites (mainly phytohormones) by endophytes was found to be the main reason for this effect (Khan et al, 2012a;2012b;Jusoh et al, 2015).…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…In the current study, the combination of gibberellin and IAA-producing endophyte (e.g. G. geotrichum) with BC increased fatty acid content; however, various studies obtained the same results for the association of endophytic fungi with their host plants (Khan et al, 2012a;2012b). In these and other studies, the production of secondary metabolites (mainly phytohormones) by endophytes was found to be the main reason for this effect (Khan et al, 2012a;2012b;Jusoh et al, 2015).…”
Section: Discussioncontrasting
confidence: 39%
“…G. geotrichum) with BC increased fatty acid content; however, various studies obtained the same results for the association of endophytic fungi with their host plants (Khan et al, 2012a;2012b). In these and other studies, the production of secondary metabolites (mainly phytohormones) by endophytes was found to be the main reason for this effect (Khan et al, 2012a;2012b;Jusoh et al, 2015). Furthermore, GA production by endophytes (Khan et al, 2012a;2012b) and the exogenous application of IAA (Jusoh et al, 2015) have been reported to modulate fatty acids in plants under normal and stress conditions.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…and Mortierella. Some of these organisms are known to have positive benefits to the plants by increasing plant growth, preventing oxidative damage, mitigating salt stress, transferring nitrogen from insect to plant and/or acting as entomopathogens [62], [63]. Neonectria is known as an opportunistic plant pathogen in some environments; however their function within native rhizosphere habitats of P. deltoides remains undefined.…”
Section: Discussionmentioning
confidence: 99%